CAPITAL BUDGETING STRATEGIES FOR SUSTAINABLE FOOD AND BEVERAGES SME’S (CASE STUDY: NASI PEDA PELANGI) - Fahriandi, Dwika; Nainggolan, Yunieta Anny (Jurnal Manajemen dan Profesional, 2025)
Nasi Peda Pelangi, a sustainability-focused F&B business, plans to expand to Tegalalang, Bali. This study evaluates the investment feasibility using capital budgeting metrics, showing positive results: NPV of IDR 686,496,320, IRR of 17.09%, PI of 1.36, and a four-year payback period. A quantitative approach analyzes financial data (2020– 2023), supported by PESTEL and SWOT analyses. Key risks include market competition, economic fluctuations, and operational uncertainties, with raw material and operating costs identified as critical factors. Effective cost management and adaptive strategies are essential for long-term profitability. The study confirms the expansion is financially viable and aligns with sustainability principles, offering insights for other F&B businesses aiming for sustainable growth.